Controversies in macroeconomic - Chrystal, K. A. (Oxford, 1979)
The new edition of this highly successful text again reviews the Keynesian, Monetarist and Neo-Classical approaches to the explanation of macroeconomic phenomena. The book is particularly notable for its clarity and brevity and although slightly more difficult than the first edition, is again aimed at intermediate level courses in macroeconomics. The particular importance of the impact of North Sea oil on the UK economy is discussed in some detail and there is a simple introduction to the theory of rational expectations.
Keywords: Macroeconomics